Effects of acupuncture on pregnancy outcomes in infertile women with polycystic ovarian syndrome: a protocol for systematic review and meta-analysis - Xiaoyan Wang; Huanfang Xu; Yigong Fang; Jiashan Li; Tian Hang (BMJ Open)
Introduction Polycystic ovarian syndrome (PCOS) is a common endocrine disorder that affects reproductive-age women, impairing their ability to conceive and sustain fertility. The efficacy of conventional therapies varies among individuals and is often accompanied by multiple side effects. Acupuncture has shown potential in fertility management for PCOS patients. However, the current evidence on its impact on pregnancy outcomes remains inconclusive. This study aims to synthesise the latest evidence regarding the efficacy and safety of acupuncture in infertile women with PCOS.Methods and analysis A comprehensive literature review will be conducted by searching for randomised controlled trials of acupuncture for infertile women with PCOS in English and Chinese language databases, including the Cochrane Database of Clinical Trials, PubMed, EMBASE, CNKI, Wanfang, VIP and SinoMed. The primary outcome will be live birth rat (LBR) and clinical pregnancy rate (CRP). The secondary outcomes will include multiple pregnancy rate (MPR), ongoing pregnancy rate (OPR), miscarriage rate (MR), ovulation rate (OR), hyperstimulation ovarian syndrome (OHSS) and adverse events. The risk of bias will be assessed using the Cochrane Risk of Bias 2.0 tool. Meta-analysis will be conducted to synthesise the evidence for each outcome, if possible. The heterogeneity will be statistically assessed using a χ2 test and I2 statistic. Subgroup analyses, sensitivity analyses and publication bias will be performed if the available data are sufficient. Evidence strength will be graded using the Grading of Recommendations Assessment, Development and Evaluation system. This protocol is developed following the guidelines of PRISMA-P 2015.Ethics and dissemination Ethics approval is not required for this review. Our findings will be published in a peer-reviewed journal.Prospero registration number CRD42024601226.